Potential of Pilsbryoconcha exilis Clam Floss as a Protein and Amino Acid Source for Stunting Prevention in Pregnant Women - Aslinda, Wery; Faisal, Elvirah; Ansar, Ansar; Lewa, Abd. Farid; Nurjaya, Nurjaya (Jurnal Bidan Cerdas, 2024)
Introduction: Stunting in children is associated with low concentrations of protein and amino acids in blood serum, which can potentially be prevented by consuming essential nutrients during pregnancy. Pilsbryoconcha exilis clam, highly available in Morowali, Central Sulawesi, is currently used to produce floss dishes. This study aimed to calculate the potential of protein and amino acids in clam floss (Pilsbryoconcha exilis) as an alternative dish to prevent stunting in pregnant women. Methods: This quantitative descriptive study compared the Recommended Dietary Allowances (RDA) for pregnant women with the content analysis of clam floss (Pilsbryoconcha exilis). Protein analysis was conducted using the AOAC method, while amino acid analysis was performed using HPLC. Results: The potential protein intake from clam floss was 223.07 g/kg body weight per day. The essential and non-essential amino acid content in clam floss (g/kg body weight per day) was as follows: histidine (5.47), isoleucine (3.62), leucine (5.04), lysine (4.8), methionine + cystine (9.65), phenylalanine + tyrosine (3.67), threonine (3.51), tryptophan (50.3), and valine (3.85). Conclusion: The potential of protein and amino acids in clam floss is concluded to be an average of 223.07 g/day and 9.98 g/kg body weight per day, respectively. Clam floss could serve as an alternative dish for pregnant women to prevent stunting. Further research considering in-vivo evaluations is encouraged.